IP-10 Promotes Latent HIV Infection in Resting Memory CD4+ T Cells via LIMK-Cofilin Pathway - Wang, Zhuo; Yin, Xiaowan; Ma, Meichen; Ge, Hongchi; Lang, Bin; Sun, Hong; He, Sijia; Fu, Yajing; Sun, Yu; Yu, Xiaowen; Zhang, Zining; Cui, Hualu; et al. (Frontiers in Immunology, 2021)
A major barrier to HIV eradication is the persistence of viral reservoirs. Resting CD4+ T cells are thought to be one of the major viral reservoirs, However, the underlying mechanism regulating HIV infection and the establishment of viral reservoir in T cells remain poorly understood. We have investigated the role of IP-10 in the establishment of HIV reservoirs in CD4+ T cells, and found that in HIV-infected individuals, plasma IP-10 was elevated, and positively correlated with HIV viral load and viral reservoir size. In addition, we found that binding of IP-10 to CXCR3 enhanced HIV latent infection of resting CD4+ T cells in vitro. Mechanistically, IP-10 stimulation promoted cofilin activity and actin dynamics, facilitating HIV entry and DNA integration. Moreover, treatment of resting CD4+ T cells with a LIM kinase inhibitor R10015 blocked cofilin phosphorylation and abrogated IP-10-mediated enhancement of HIV latent infection. These results suggest that IP-10 is a critical factor involved in HIV latent infection, and that therapeutic targeting of IP-10 may be a potential strategy for inhibiting HIV latent infection.